Enhancement of physical properties in partially crosslinked waste high density polyethylene - Lee, Jong Rok; Lee, Dong Gun; Hong, Soon Man; Kang, Ho-Jong (POLYMER SOC KOREA, 2007)
The characteristics of crosslinking and physical properties in partially crosslinked waste high density polyethylene (HDPE) were studied by introducing reactive melt processing with perbutyl peroxide (PBP). It was found that impurities in waste HDPE affected the crosslinking kinetics. Decrease in density and heat of fusion were observed in partially crosslinked HDPE while its melt viscosity increased. It was explained that impurities in waste HDPE enhanced the crosslinking compared to pure HDPE. As a result, dramatic mechanical property improvement was achieved in the waste HDPE by crosslinking reaction.